2014
DOI: 10.1016/j.bpj.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Pathway of Magnesium Influx in Rat Ventricular Myocytes

Abstract: Cytoplasmic free Mg(2+) concentration ([Mg(2+)]i) was measured in rat ventricular myocytes with a fluorescent indicator furaptra (mag-fura-2) introduced by AM-loading. By incubation of the cells in a high-K(+) (Ca(2+)- and Mg(2+)-free) solution, [Mg(2+)]i decreased from ? 0.9 mM to 0.2 to 0.5 mM. The lowered [Mg(2+)]i was recovered by perfusion with Ca(2+)-free Tyrode's solution containing 1 mM Mg(2+). The time course of the [Mg(2+)]i recovery was fitted by a single exponential function, and the first derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
5
27
0
Order By: Relevance
“…TRPM7‐like currents in both cell types were activated by a reduction of [Mg 2+ ] i , an elimination of extracellular divalent cations, and were inhibited by 2‐APB, NS8593, and FTY720 (Figs. and ), which were consistent with previous reports (Nadler et al ; Schmitz et al ; Chubanov et al ; Chokshi et al ,; Qin et al ; Tashiro et al , ). We previously reported that TRPM7 current was inhibited by H 2 O 2 in a [Mg 2+ ] i ‐ and [ATP] i ‐dependent manner in HEK293 cells overexpressing murine TRPM7 (Inoue et al ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…TRPM7‐like currents in both cell types were activated by a reduction of [Mg 2+ ] i , an elimination of extracellular divalent cations, and were inhibited by 2‐APB, NS8593, and FTY720 (Figs. and ), which were consistent with previous reports (Nadler et al ; Schmitz et al ; Chubanov et al ; Chokshi et al ,; Qin et al ; Tashiro et al , ). We previously reported that TRPM7 current was inhibited by H 2 O 2 in a [Mg 2+ ] i ‐ and [ATP] i ‐dependent manner in HEK293 cells overexpressing murine TRPM7 (Inoue et al ).…”
Section: Discussionsupporting
confidence: 93%
“…Whole‐cell patch‐clamp recordings were performed to investigate whether native mouse white adipocytes functionally express TRPM7 current. It has been reported that TRPM7 is (1) inhibited by intracellular Mg 2+ (Nadler et al ; Schmitz et al ; Chokshi et al ,); (2) activated by the elimination of divalent cations from the bath solutions, resulting in quasi‐linear current‐voltage ( I – V ) relationships (Nadler et al ; Kerschbaum et al ; Inoue et al ); (3) inhibited by H 2 O 2 irreversibly in a [Mg 2+ ] i ‐dependent manner (Inoue et al ); and (4) inhibited by 2‐aminoethyl diphenylborinate (2‐APB) (Li et al ; Macianskiene et al ; Chokshi et al ), N‐methyl maleimide (NMM) (Inoue et al ), NS8593 (Chubanov et al ; Tashiro et al , ), and FTY720 (Qin et al ; Takahashi et al ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of TRPM7 currents by naltriben have previously been confirmed in primary ventricular myocytes [16], as well as in HEK293 cells overexpressing TRPM7 [14]. In the current study, we first verified the potentiating effect of naltriben on the endogenous TRPM7-like currents in U87 cells by whole-cell patch-clamp recording.…”
Section: Resultssupporting
confidence: 62%
“…The involvement of these channels in impaired cardiac automaticity and conduction defects has been implicated with a TRPM7 knock-in mouse model [31,32]. In addition, TRPM7-like currents have been measured in ventricular cells of various animal species [33,34] as well as in human atrial cardiomyocytes [16,29,30], and CAR, at a concentration of 100 μM, almost completely blocked that current [16]. The TRPM7 channels are ubiquitous Mg 2+ and Ca 2+ permeable [35] and are thought to be responsible for Mg 2+ transport into the cell at negative membrane potentials.…”
mentioning
confidence: 99%